The transformation of local folktales story into mobile games application: a case study of Hikayat Sang Kancil and Gagak yang bijak / Mohd Hisham Johari - Johari, Mohd Hisham (2015)
Malaysia are enrich with lots of folktales story. With more than 366 recorded literatures that teach good morale. Unfortunately, these precious treasures are fading form the memory of Malaysian society. With the rapid modernization take place, Malaysian is more exposed to the western folktales. Previously, this folktales story are told verbally form one to another, but younger generation nowadays prefer screen based material. This study will research on the use of mobile games as a medium to promote local folktales. It is important to seek a better understanding on how mobile game can be used to educate parallel with the development of technology. The objective of this research is to identify the most suitable content in design and gameplay that can be developed into a mobile games story telling application and to measure the effectiveness of the mobile games regarding this issue. Mix method has been practice in this research which is qualitative and quantitative. A survey and interviews has been conducted in order to gather data. Researcher found that the use of mobile games can be used as a medium in promoting local folktales. The researcher also found that different game genre contributes to different feedbacks.